4+-2.2h=-3.7

Simple and best practice solution for 4+-2.2h=-3.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+-2.2h=-3.7 equation:


Simplifying
4 + -2.2h = -3.7

Solving
4 + -2.2h = -3.7

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -2.2h = -3.7 + -4

Combine like terms: 4 + -4 = 0
0 + -2.2h = -3.7 + -4
-2.2h = -3.7 + -4

Combine like terms: -3.7 + -4 = -7.7
-2.2h = -7.7

Divide each side by '-2.2'.
h = 3.5

Simplifying
h = 3.5

See similar equations:

| -7x-1+8=7 | | c=400-5x+0.135x^2 | | -(-8x-3)-1x=4x+6(-5+1x) | | 13x-(x-7)=29 | | 14v+6=2(75+7v)-4 | | 4(x+5)=-2(x+1) | | 3tan^2(pi)-1=0 | | -8(6k+4)=-128 | | 16x^2-32x+18=0 | | -16g+3h-19h-4g-16h= | | j+2=9 | | 42y=32x+340 | | -40-(2x+5)=-60 | | t=(3.28+7.18)4.6 | | 3x+2-4(x+1)=5x+22 | | 2(5x-6)+6(5x-7)=-54 | | 6.05=2.25m+.2 | | 3G-2(g+4)=8g-8 | | 12(2p-3)=99-9p | | -(-8x-7m)=5m-7(-3-1m) | | 60=6(6-12n) | | x+2-4(x+1)=5x+22 | | -7x/5=3/10 | | 7x+5=5x+16 | | 1+7p-7p=4 | | 7y=3y+32 | | -(7x/5)=3/10 | | -5=-x+5y | | d+-3=-10 | | 4x+6.66666666666666666666666666y=500 | | f=4(3+4)-2 | | 2x+16=4x-15 |

Equations solver categories